The Political Economy of the One Belt One Road Initiative and its Impact on EU-China Relations - Bednářová, Dita; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The thesis deals with the contemporary economic partnership between the European Union and the People's Republic of China with an emphasis being placed on the Belt and Road Initiative. The aim of the thesis is to create a comprehensive overview of the key milestones in EU-China Economic Relations and focus on the current challenges in the partnership. The thesis will evaluate the potential of the Belt and Road Initiative from the perspective of realized investments in the EU and deliberate about the motive behind the Initiative. The first chapter of the thesis brings forward the theory of International Political Economy which will be used as a basis for the explanation of contemporary China's Foreign Policy and its narrative. The second chapter will present the key milestones of EU-China Economic Relations with the main focus placed on trade barriers, disputes within the WTO and investments relations. Further, the thesis will introduce the Belt and Road Initiative and its main objectives. The last chapter will present the major investments realized within the Initiative and judge the prospects and perils of the Initiative for the future EU-China Economic Relations.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: evropská integrace [obor dipl. práce]; diplomové práce; master's theses